A comparison of the impact of current smoking on 2-year major clinical outcomes of first- and second-generation drug-eluting stents in acute myocardial infarction: Data from the Korea Acute Myocardial Infarction Registry. Issue 10 (March 2019) - Kim, Yong Hoon; Her, Ae-Young; Jeong, Myung Ho; Kim, Byeong-Keuk; Hong, Sung-Jin; Ahn, Chul-Min; Kim, Jung-Sun; Ko, Young-Guk; Choi, Donghoon; Hong, Myeong-Ki; Jang, Yangsoo
Abstract : Abstract: There are limited studies comparing the effect of current smoking on first-generation (1G)-drug-eluting stents (DES) and second-generation (2G)-DES in acute myocardial infarction (AMI) patients after successful percutaneous coronary intervention (PCI). We investigated the clinical impact of current smoking on 2-year clinical outcomes between the 1G-DES and the 2G-DES in AMI patients after PCI. A total of 11, 812 AMI patients with a history of current smoking who underwent successful PCI with 1G-DES (n = 4622) or 2G-DES (n = 7190) were enrolled. The primary endpoint was the occurrence of major adverse cardiac events (MACE) defined as all-cause death, recurrent AMI (re-MI) or any revascularization (target lesion revascularization [TLR], target vessel revascularization [TVR], and non-TVR). The secondary endpoint was the incidence of definite or probable stent thrombosis (ST). Two propensity score-matched (PSM) groups (3900 pairs, n = 7800, C-statistic = .708) were generated. After PSM analysis, the 2-year cumulative incidence of MACE was significantly higher in the 1G-DES group compared with the 2G-DES (9.4% vs 7.4%, Log-rank P  = .002; hazard ratio, 1.281; 95% confidence interval, 1.097–1.495; P  = .002) and this increased incidence of MACE was associated with the increased incidence of any revascularization including TLR, TVR, and non-TVR. However, the incidences of ST, all-cause death, re-MI were not significantly different during 2-year follow-up period. 2G-DES was the preferred treatment strategy for AMI patients with a history of current smoking to reduce MACE especially, any revascularization rate rather than 1G-DES in this study.